2015
DOI: 10.1177/0040517515591776
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reactive dyes on ultraviolet protection of cotton knitted fabrics with different fabric constructions

Abstract: The influence of coloration on ultraviolet (UV) protection of cotton knitted fabrics with different knit structures incorporated with the three major stitch types, namely knit, tuck and miss stitches, are studied in four approaches. The effects of color depth and knit structures on the ultraviolet protection factor (UPF) of fabrics are investigated. The influences of hue and color depth on the UPF of fabrics are also compared. Since UV protection offered by dyes mainly depends on their chemical structures, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…When a mask is available in multiple colors, black and blue make a better choice. 26,31 The darkness of a shade also correlates, albeit weakly, with UPF. 26 Nevertheless, the bottom line is that the depth/strength of a color is the most important factor as it indicates a higher concentration of UV-absorbing dye molecules.…”
Section: Color and Dyesmentioning
confidence: 99%
See 2 more Smart Citations
“…When a mask is available in multiple colors, black and blue make a better choice. 26,31 The darkness of a shade also correlates, albeit weakly, with UPF. 26 Nevertheless, the bottom line is that the depth/strength of a color is the most important factor as it indicates a higher concentration of UV-absorbing dye molecules.…”
Section: Color and Dyesmentioning
confidence: 99%
“…26 The color of a fabric is only its reflection in the visible spectrum and unfortunately doesn't correlate well with its absorbance in the UV spectrum. 26 The chemical composition of dye molecules holds greater weight on the resulting UPF than the hue or darkness of the fabric. 9,26 Many studies demonstrate the large impact that colorants and chemical finishing compounds can have on UPF.…”
Section: Color and Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various kind of synthetic dyes are commercially available to enhances the UPF of the fabric. Direct, vat and reactive dyes increases the UPF of fabric [85][86][87]. Various researches reported that natural dyes can also enhances the UPF of the fabric.…”
Section: Uv Protective Dyesmentioning
confidence: 99%
“…[1][2][3] Dyeing of cotton fabrics with reactive dye is an extremely complex process which must take into account a large number of physical and chemical properties, such as fiber micronaire/maturity, reactive dye affinity, dyeing methods, dyeing equipment, dye dosage, electrolyte concentration, pH value, dyeing time, temperature, pressure, and dye liquor circulation speed in the dye-bath. [4][5][6][7][8] While modern dyeing factories can carefully control these factors, there are other parameters which are less easily controlled, such as water quality, atmospheric pressure conditions, measuring instrument errors, dyeing equipment errors, and operator experience. 9 Practice has shown that to achieve high one-time success at low costs, it is necessary to improve the dyeing device and the equipment level, control accurately dyeing process and quality of dyeing products and optimize dye concentrations and processing conditions.…”
mentioning
confidence: 99%